Detachment of the remora suckerfish disc: kinematics and a bio-inspired robotic model. (21st August 2020) - Wang, Siqi; Li, Lei; Sun, Wenguang; Wainwright, Dylan; Wang, He; Zhao, Wei; Chen, Bohan; Chen, Yufeng; Wen, Li
Abstract: Remora suckerfish can attach to a wide diversity of marine hosts, however, their detachment mechanism remains poorly understood. Through analyzing high-speed videos, we found that the detachment of the live remora ( Echeneis naucrates ) is a rapid behavior that can happen within 240 ms. We separate this remarkable behavior into three stages: 1) lamellae folding down and soft lip curling, 2) disc raising and 3) complete detachment. To quantitatively investigate the detachment behavior, we fabricated a multi-material biomimetic disc and utilized it to study each stage of the detachment process. In stage one, we found that folding down lamellae is essential for decreasing the detachment resistance (vertical interfacial force and friction force) of the suction disc. Also, curling up the soft lip to breaking the adhesive seal reduced the vertical pull-off force up to 94 times. During disc raising in stage 2, we found that the partially flexible base (Young's modulus: ∼3 MPa) of the disc can lead to a 30% power-use reduction compared to a rigid base (Young's modulus: ∼3 GPa). After completing full detachment in stage 3, the corresponding drag wake flow decreased by 44% compared to an attached state due to lamellae folding and the entire soft lip uncurling. We developed a bio-inspired remora suckerfish robot propelled by a water jet to demonstrate a complete detachment which covers all three stages within 200 ms. We also demonstrated that an ROV has both hitchhiking and pick-and-place capabilities by integrating remora-inspired discs at appropriate locations. This study may shed light on future research in bio-inspired adhesives and lay a foundation for developing an untethered, multimodal, underwater hitchhiking robot.